Epidemiological and genomic characteristics of global mcr-positive Escherichia coli isolates - Shi, Jiping; Zhu, Hong; Liu, Chang; Xie, Hui; Li, Chuchu; Cao, Xiaoli; Shen, Han (Frontiers in Microbiology, 2023)
Objective: The worldwide dissemination of colistin-resistant Escherichia coli (E. coli) endangers public health. This study aimed to better understand the global genomic epidemiology of E. coli isolates carrying mobilized colistin resistance (mcr) genes, providing information to assist in infection and prevention. Methods: E. coli genomes were downloaded from NCBI and mcr was detected using BLASTP. Per software was used to extract information on hosts, resources, collection data, and countries of origin from GenBank. Sequence types (STs), prevalence of plasmids, antimicrobial resistance genes (ARG), and virulence factors (VF) in these genomes were analyzed. Statistical analyses were performed to assess the relationships between mcr, ARGs, plasmids, and STs. Results: In total, 778 mcr-positive isolates were identified. Four mcr variants were detected, with mcr-1 (86.1%) being the most widespread, followed by mcr-9 (5.7%), mcr-5 (4.4%), and mcr-3 (3.0%). Multiple ARGs were identified, with blaCTX-M (53.3%), fosA (28.8%), qnr (26.1%), blaNDM (19.8%), and aac(6’)-Ib-cr (14.5%) being the most common. Overall, 239 distinct STs were identified, of which ST10 (13.8%) was the most prevalent. A total of 113 different VFs were found, terC (99.9%) and gad (83.0%) were most frequently detected. Twenty types of plasmids were identified; IncFIB (64.1%), IncX (42.3%), and IncX (42.3%) were the most common replicons. IncI2 and IncX4 were frequently detected in mcr-1-positive isolates, whereas IncFII, IncI1-I, and IncHI2 were dominant plasmids in mcr-3, mcr-5, and mcr-9-positive isolates, respectively. A higher frequency of ARGs and VFs was observed among ST156 and ST131 isolates. Conclusion: Our data indicated that more than half of the mcr-positive E. coli strains carried endemic ARGs and VFs. ST10 and ST156 isolates deserved further attention, given the rapid transmission of ST10 and the convergence of ARGs and VFs in ST156.